FAMILY PLANNING PROGRAM WITH FOUR CHILDREN CRITICAL STUDIES ON THE NEW FAMILY PLANNING POLICY OF BALI GOVERNOR - Pujaastawa, Ida Bagus Gde (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
This paper tries to examine the policy of the Governor of Bali, I Wayan Koster, in the form of the Governor of Bali's Instruction Number 1545 of 2019 concerning the Promotion of the Krama Bali Family Planning Program. This instruction was made several months after he was appointed as Governor of Bali. Through these instructions he recommended that the people of Bali implement a Family Planning Program with four children. Many of these instructions reap the pros and cons in the Balinese community. Some parties are supportive, because looking at the Krama Bali Family Planning Program with four children in addition to an appreciation of reproductive rights, as well as the preservation of ancestral cultural heritage. While some others opposed, because they considered the instruction to be contrary to the policy of the National Family Planning Program with two children that had been set by the central government since 1970. The birth of the Governor of Bali's Instruction Number 1545 of 2019 on the Promotion of the Krama Bali Family Planning Program was a sufficient phenomenon interesting to study. The results of the analysis of this issue concluded that the instructions of the Governor of Bali regarding the Promotion of the Krama Bali Family Planning Program could be seen as a form of resistance to central hegemony which could threaten the existence of a sociocultural system of Bali as a sociocultural system of minority groups. However, the demographic developments that will occur due to the governor's instructions are also feared to cause changes in the conditions of material infrastructure which are the buffer bases and in turn will cause changes in the structural and superstructure aspects.